Synthesis of new azo dyes via Suzuki coupling - Ali G. Khadim (Al-Qadisiyah Journal of Pure Science, 2017)
The synthesis of new azo dyes have been achieved by coupling reaction ofpyrimidine derivative with different phenolic compounds , the products have beentreated with 2- fluoro boronic acid by Suzuki coupling reaction to give new azo dyes .These compounds have been characterized by spectroscopic methods (FTIR , UVVIS),TLC and melting point .